Large area CMOS active pixel sensor x‐ray imager for digital breast tomosynthesis: Analysis, modeling, and characterization. Issue 11 (8th October 2015) - Zhao, Chumin; Kanicki, Jerzy; Konstantinidis, Anastasios C.; Patel, Tushita
Abstract : Purpose: Large area x‐ray imagers based on complementary metal‐oxide‐semiconductor (CMOS) active pixel sensor (APS) technology have been proposed for various medical imaging applications including digital breast tomosynthesis (DBT). The low electronic noise (50–300 e − ) of CMOS APS x‐ray imagers provides a possible route to shrink the pixel pitch to smaller than 75 μm for microcalcification detection and possible reduction of the DBT mean glandular dose (MGD). Methods: In this study, imaging performance of a large area (29 × 23 cm 2 ) CMOS APS x‐ray imager [Dexela 2923 MAM (PerkinElmer, London)] with a pixel pitch of 75 μm was characterized and modeled. The authors developed a cascaded system model for CMOS APS x‐ray imagers using both a broadband x‐ray radiation and monochromatic synchrotron radiation. The experimental data including modulation transfer function, noise power spectrum, and detective quantum efficiency (DQE) were theoretically described using the proposed cascaded system model with satisfactory consistency to experimental results. Both high full well and low full well (LFW) modes of the Dexela 2923 MAM CMOS APS x‐ray imager were characterized and modeled. The cascaded system analysis results were further used to extract the contrast‐to‐noise ratio (CNR) for microcalcifications with sizes of 165–400 μm at various MGDs. The impact of electronic noise on CNR was also evaluated. Results: The LFW mode shows better DQE at low air kerma ( Ka < 10 μ Gy) and should be used for DBT. At current DBT applications, air kerma ( Ka ∼ 10 μ Gy, broadband radiation of 28 kVp), DQE of more than 0.7 and ∼0.3 was achieved using the LFW mode at spatial frequency of 0.5 line pairs per millimeter (lp/mm) and Nyquist frequency ∼6.7 lp/mm, respectively. It is shown that microcalcifications of 165–400 μm in size can be resolved using a MGD range of 0.3–1 mGy, respectively. In comparison to a General Electric GEN2 prototype DBT system (at MGD of 2.5 mGy), an increased CNR (by ∼10) for microcalcifications was observed using the Dexela 2923 MAM CMOS APS x‐ray imager at a lower MGD (2.0 mGy). Conclusions: The Dexela 2923 MAM CMOS APS x‐ray imager is capable to achieve a high imaging performance at spatial frequencies up to 6.7 lp/mm. Microcalcifications of 165 μm are distinguishable based on reported data and their modeling results due to the small pixel pitch of 75 μm. At the same time, potential dose reduction is expected using the studied CMOS APS x‐ray imager.